Building an Ethical Culture in The Workplace Through Responsible Leadership and Employee Ethical Efficacy - Hermanto, Bambang; Ferdianto, Jemmy Regri; Wibisono, Aryo (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2025)
This research falls within the field of organizational behavior with a focus on the role of responsible leadership in shaping ethical workplace culture. The purpose of this study is to analyze the effect of responsible leadership on employee ethical voice through the mediating role of ethical efficacy. The study was conducted on 90 employees of Micro, Small, and Medium Enterprises (MSMEs) in Sumenep Regency. A quantitative approach was employed in this research using the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis technique. The findings indicate that responsible leadership has a significant effect on employees’ ethical efficacy, which in turn positively mediates the relationship between leadership and ethical voice behavior. These findings contribute theoretically to the literature on leadership and organizational ethics, particularly in the MSME context. Practically, the results serve as an important reference for MSME stakeholders in fostering a workplace culture that encourages ethical expression. The conclusion of this study emphasizes the importance of responsible leadership in strengthening employees’ ethical attitudes and psychological empowerment to build organizations with integrity.